2013
DOI: 10.7861/clinmedicine.13-6-s50
|View full text |Cite
|
Sign up to set email alerts
|

Joint hypermobility: emerging disease or illness behaviour?

Abstract: -Joint hypermobility syndrome is a common clinical entity which is much misunderstood, overlooked, misdiagnosed and mistreated. It was first described in the 1960s as a purely musculoskeletal condition due to joint laxity and hypermobility occurring in otherwise healthy individuals. Some four decades later it is now perceived to be a multi-systemic heritable disorder of connective tissue with manifestations occurring far beyond the confines of the locomotor system and with ramifications potentially affecting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Joint Hypermobility Syndrome is considered to be synonymous with EDS-hypermobility type (Grahame, 2013; Tinkle et al, 2009). An updated classification of the diagnostic criteria for the various Ehlers-Danlos syndromes has been published (Malfait et al, 2017), which includes hypermobile Ehlers-Danlos syndrome.…”
Section: Joint Hypermobility Syndrome/ehlers-danlos Syndrome-hypermobmentioning
confidence: 99%
“…Joint Hypermobility Syndrome is considered to be synonymous with EDS-hypermobility type (Grahame, 2013; Tinkle et al, 2009). An updated classification of the diagnostic criteria for the various Ehlers-Danlos syndromes has been published (Malfait et al, 2017), which includes hypermobile Ehlers-Danlos syndrome.…”
Section: Joint Hypermobility Syndrome/ehlers-danlos Syndrome-hypermobmentioning
confidence: 99%
“…Although EDS-HT is the most common type and the least severe type of EDS, it tends to be underdiagnosed and mistreated, sometimes leading to severe disability that may have been preventable if diagnosed and treated properly 64,81,82. A survey among physiotherapists in the UK found that only 32% of respondents received formal training in EDS-HT management 83.…”
Section: General Remarksmentioning
confidence: 99%
“…EDS hypermobility type, the most common sub-type, has similar symptoms and diagnostic criteria as HMS, so clinically discriminating between them can be challenging [9]. Before 2017, the Villefranche nosology was a common tool for diagnosis of 6 different forms of EDS [11] as well as the Brighton criteria for HMS [12]. An overview of the changes is available in Supplementary Material (Tables S1 and S2).…”
Section: Introductionmentioning
confidence: 99%